Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1159/000448515
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalisations with Hidradenitis Suppurativa: An Increasing Problem That Deserves Closer Attention

Abstract: Background/Aims: Hidradenitis suppurativa (HS), a chronic inflammatory skin disease of the hair follicle, can lead to scarring and disability. With an estimated European prevalence of 1%, few epidemiological studies of HS have been performed, and none focused on hospitalisations. We aimed to study the time trends of HS hospitalisations and to evaluate the demographic characteristics, hospital incidence rate, readmissions, length of stay, comorbidities and risk factors of hospitalised HS patients. Methods: We p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
47
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 31 publications
2
47
0
3
Order By: Relevance
“…In the present cohort of 2465 patients with HS, using data from 14 centres from different countries, we observed a prevalence of 27% for IGF skin lesions. The exact prevalence remains elusive, but studies using diverse cohorts provide estimates of 4.6–30% for PSD in patients with HS . Therefore, a direct and statistically significant comparison with the general population is still warranted, but the proportion of PSD within this HS cohort seems to be higher than the 1–9% prevalence observed in the general population .…”
Section: Discussionmentioning
confidence: 88%
“…In the present cohort of 2465 patients with HS, using data from 14 centres from different countries, we observed a prevalence of 27% for IGF skin lesions. The exact prevalence remains elusive, but studies using diverse cohorts provide estimates of 4.6–30% for PSD in patients with HS . Therefore, a direct and statistically significant comparison with the general population is still warranted, but the proportion of PSD within this HS cohort seems to be higher than the 1–9% prevalence observed in the general population .…”
Section: Discussionmentioning
confidence: 88%
“…18,21 6. EPIDEMIOLOGY HS is an under recognized entity with a significant delay from the onset of symptoms to the diagnosis, 22,23 with a median delay of 12 years in one study. 24 Prevalence is a matter of debate, with estimated rates as low as 0.00033% up to 4%.…”
Section: Psychosocial Impactmentioning
confidence: 93%
“…22 and involved areas also differ between genders, with the groin and submammary regions most commonly affected in women while the buttocks and perianal skin are the most affected areas in men. 22 Chronicity is the rule in HS. In a questionnaire survey the mean duration of the active disease was 18.8 years.…”
Section: Prognosismentioning
confidence: 99%
See 1 more Smart Citation
“…In Europe, HS prevalence in the general population is estimated to be around 1%, although only few studies have assessed this prevalence . In a previous study, the authors reported an increasing trend in the HS hospital incidence rate. This study aims to measure the frequency of hospitalizations with HS in Portuguese public hospitals, during a 15‐year period, in order to estimate the proportion of HS patients who sought healthcare services.…”
mentioning
confidence: 99%